2021
DOI: 10.1177/14614448211032965
|View full text |Cite
|
Sign up to set email alerts
|

A social semiotic perspective on emoji: How emoji and language interact to make meaning in digital messages

Abstract: This article presents a social semiotic analysis of emoji-language semiosis. Combining the theoretical architecture of Systemic Functional Linguistics and methodology of Multimodal Discourse Analysis, we propose an analytical framework that can identify how emoji make meaning both individually and in interaction with language. Using the web-based coding software WebAnno, we apply this framework to a dataset of text messages and social media posts. The results identify typical realisations of particular semioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 47 publications
0
19
0
3
Order By: Relevance
“…On the other hand, we found expressions that praised the content created by TikTokers: "your transitions are amazing 💯💞💪,'' "look at that picture quality," "those transitions are cleaner than my face 😳,'' "super talented 😻❤,'' and "you are a crack and you deserve to be duetted." In most cases we observed that comments introduced multiple emoji with attitudinal meaning that differed from the linguistic prosodic pattern, making evident other emotions (Logi & Zappavigna, 2021). For the cases previously reported, we found facial expressions that consumer science scholars Jaeger and Ares (2017) classified as (a) 🙂 = happy, satisfied; (b) 😍 = excited, happy; and (c) 😳 = surprised, shocked.…”
Section: Supporting Marginalized Groups Through Polarity and Subjectivitymentioning
confidence: 55%
See 1 more Smart Citation
“…On the other hand, we found expressions that praised the content created by TikTokers: "your transitions are amazing 💯💞💪,'' "look at that picture quality," "those transitions are cleaner than my face 😳,'' "super talented 😻❤,'' and "you are a crack and you deserve to be duetted." In most cases we observed that comments introduced multiple emoji with attitudinal meaning that differed from the linguistic prosodic pattern, making evident other emotions (Logi & Zappavigna, 2021). For the cases previously reported, we found facial expressions that consumer science scholars Jaeger and Ares (2017) classified as (a) 🙂 = happy, satisfied; (b) 😍 = excited, happy; and (c) 😳 = surprised, shocked.…”
Section: Supporting Marginalized Groups Through Polarity and Subjectivitymentioning
confidence: 55%
“…This issue was mainly due to the limited posts created for #ThisIsMeChallenge. In addition, we noted that the SA approach was created by predesigned algorithms that did not provide a semiotic discourse analysis of aspects such as emojis (Logi & Zappavigna, 2021), which produced biases between polarity-subjectivity and reality. Accordingly, we suggest that future research approaches music empowerment on social media using the proposed codebook, as well as diving deeper into the aspects that make music a transmedia storytelling tool for platforms such as TikTok.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have addressed the meaning, function, and usage of each type of graphicon in different cultural contexts (e.g., Al Rashdi, 2018;Ge, 2020;Ge & Herring, 2018;Logi & Zappavigna, 2021;Sampietro, 2019). Interrelations among the three types, however, have not attracted much attention until recently.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on emoji meaning have ranged from how emoji supplement text with pragmatic information like irony (Garcia et al, 2022;Weissman & Tanner, 2018), emotional valence (Pfeifer et al, 2022), and indirect meaning (Holtgraves & Robinson, 2020) to more direct investigations of emoji meaning ratings and norms (Rodrigues et al, 2018;Was & Hamrick, 2021). In light of the wide range of communicative functions that emoji can fulfill (e.g., Beißwenger & Pappert, 2019;Dainas & Herring, 2021;Ge & Herring, 2018;Logi & Zappavigna, 2021;Yang & Liu, 2021), the nature of emoji meanings across these varied uses is rich ground for further research.…”
Section: Introductionmentioning
confidence: 99%